2007
DOI: 10.1210/jc.2006-2868
|View full text |Cite
|
Sign up to set email alerts
|

Age of Onset of Type 1 Diabetes in Children and Carotid Intima Medial Thickness

Abstract: The IMT measurement detected subclinical atherosclerosis in a large cohort of diabetic children. Systolic blood pressure, total cholesterol level, insulin dosage, and age at onset of the disease were significantly related to the IMT. Longitudinal measurements may help to identify patients at special risk for atherosclerotic changes and cardiovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
42
3
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(52 citation statements)
references
References 29 publications
6
42
3
1
Order By: Relevance
“…These results are consistent with some previous studies (Dalla Pozza et al, 2007;Krantz et al, 2004;Schwab et al, 2007), but not with other studies (EDIC, 1999;Margeirsdottir et al, 2010). In our age-specific analysis of cIMT, we found that median cIMT was significantly and equally greater in children and adolescents with type 1 diabetes when compared with controls across all age categories.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…These results are consistent with some previous studies (Dalla Pozza et al, 2007;Krantz et al, 2004;Schwab et al, 2007), but not with other studies (EDIC, 1999;Margeirsdottir et al, 2010). In our age-specific analysis of cIMT, we found that median cIMT was significantly and equally greater in children and adolescents with type 1 diabetes when compared with controls across all age categories.…”
Section: Discussionsupporting
confidence: 92%
“…The lack of a clear contribution of classical CVD risk factors to cIMT in our study and in previously published pediatric studies (Dalla Pozza et al, 2007;Dalla Pozza et al, 2011;Krantz et al, 2004;Krebs et al, 2012) may be explained by differences in age, diabetes duration, length of follow-up, and CVD risk categorization (current vs. historical data). Alternatively, the interplay between adult classical CVD risk factors may change over time and/or may contribute in a more complex way to the vascular changes and cIMT increase seen in type 1 diabetes.…”
Section: Discussioncontrasting
confidence: 64%
See 3 more Smart Citations